2013
DOI: 10.1111/fwb.12170
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and nutrient availability interact to mediate growth and body stoichiometry in a detritivorous stream insect

Abstract: Summary Regimes of temperature and nutrient availability are undergoing rapid modification at global scales. Both temperature and nutrients can influence consumer physiology and growth via several mechanisms. We examined how temperature and the nutrient content of food interact to affect consumption, growth and body stoichiometry of a detritivorous consumer (the caddisfly Pycnopsyche gentilis). In a 7‐week growth study, P. gentilis larvae were reared at two different temperatures (5 and 10 °C) while fed cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 60 publications
6
23
0
Order By: Relevance
“…Previous studies indicated potential intraspecific variation in body C ∶ P among some aquatic insects (Cross et al 2003, Small and Pringle 2010, Kendrick and Benstead 2013. In our study, oak-fed P. lepida exhibited nonstrict homeostasis (H = 4.74), whereas maple-fed P. lepida appeared to be strictly homeostatic.…”
Section: Stoichiometric Regulation By P Lepidasupporting
confidence: 48%
See 1 more Smart Citation
“…Previous studies indicated potential intraspecific variation in body C ∶ P among some aquatic insects (Cross et al 2003, Small and Pringle 2010, Kendrick and Benstead 2013. In our study, oak-fed P. lepida exhibited nonstrict homeostasis (H = 4.74), whereas maple-fed P. lepida appeared to be strictly homeostatic.…”
Section: Stoichiometric Regulation By P Lepidasupporting
confidence: 48%
“…Maximum rates of P. lepida growth in our study (0.046/d) approached or were greater than maximum growth for Pycnopsyche spp. in previous studies (0.041, 0.061, and 0.030/d; Eggert and Wallace 2003, Chung and Suberkropp 2009, Kendrick and Benstead 2013, suggesting that conditions closely approximated those of optimal growth. Moreover, despite the limitations of growth-based methods, our study shows that, compared to many bioenergetics models, growth data across varying resource C ∶ P provide a less error-prone means of estimating TER C ∶ P that more accurately represents organism stoichiometry and should be more applicable to diverse taxa.…”
Section: Caveats and Conclusionmentioning
confidence: 51%
“…This pattern is probably due to the decrease in the relative concentration of growth-limiting nutrients (N) in the system (Kendrick & Benstead, 2013;Sardans et al, 2012). This pattern is probably due to the decrease in the relative concentration of growth-limiting nutrients (N) in the system (Kendrick & Benstead, 2013;Sardans et al, 2012).…”
Section: Source Of Variationmentioning
confidence: 97%
“…The importance of the infl uence of temperature on the biology and biodynamics of pests has been increasingly studied (Nondillo et al 2008, Silva et al 2011, Kendrick and Benstead 2013. In Brazil, some insects have recently gained greater importance, and it is believed that the occurrence of higher temperatures has favored some insect pests.…”
Section: An Acad Bras Cienc (2016) 88 (2)mentioning
confidence: 99%